Consumer Trends: Exploring Shifts and Patterns in Contemporary Consumer Behavior - Karunia, Erick (The Journal of Business and Management Research, 2023)
This study explores contemporary consumer behavior trends, focusing mainly on conscious consumerism, digital transformation, and socio-cultural influences. The research design involves a comprehensive literature review spanning multiple disciplines: marketing, psychology, sociology, and anthropology. Methodologically, the study synthesizes findings from existing research to provide insights into the motivations, preferences, and behaviors of socially conscious consumers in the digital age. The findings highlight the growing importance of ethical and sustainable consumption practices among Millennials and Gen Z consumers, driven by values such as environmental stewardship and social responsibility. Moreover, the study underscores the transformative impact of digital technologies and social media platforms on consumer behavior, emphasizing the need for businesses to adapt their strategies to engage with digitally empowered consumers effectively. The study's implications suggest that companies must align their values and practices with those of socially conscious consumers, embrace digital transformation, and recognize the influence of socio-cultural factors in shaping consumer behavior. By understanding these trends and adapting their strategies accordingly, businesses can build stronger connections with consumers, foster brand loyalty, and drive sustainable growth in the global marketplace.